SOME ISSUES OF THE EDUCATIONAL EVALUATION - Wang Ziye (International Journal of Innovative Technologies in Social Science, 2024)
There are many issues that need to be addressed in the education sector today. For example, improving the learning environment, availability of textbooks, effective organization of lessons, improvement of teaching technology, and increasing student participation in unit lessons. Among these, the question of educational evaluation and its importance, in particular, how teachers and students are evaluated, the types of assessment, and whether the assessment is realistic, is important today. Evaluation is important in determining what a student’s strengths and weaknesses are, what to focus on in the future, improving curricula, increasing learning efficiency, and making educational policy decisions about students. When teachers assess students, they tend to assess how well they have memorized or memorized what they have been taught, which undermines their creativity. Moreover, the widespread use of test methods, regardless of student participation in the assessment, casts doubt on the validity of the assessment. Internationally, however, the quality of education is often measured by student achievement. Everyone knows the term education, but when asked what exactly it is, it is difficult to answer. In the twentieth century, behaviorist theorists regarded a knowledgeable person as an educated person, while in the twenty-first century constructivist theorists defined an educated person as a person with a certain level of knowledge, ability to adapt to the society in which he lives, and to work with others. The mission of this research is to clarify how to evaluate in education and offer ways to deal with them in practical applications. There are used by the educational evaluation, to create survey or checklist, to report evaluation result, all these parts of evaluation process are extensively discussed in this article. Result of this research is that compare evaluation models and define the best evaluation way in education.